2015
DOI: 10.1002/eji.201545886
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 signaling and IL‐17 expression: Defining pathways and possible therapeutic targets

Abstract: IL-17 mediates immune responses against extracellular pathogens, and it is associated with the development and pathogenesis of various autoimmune diseases. The expression of IL-17 is regulated by various intracellular signaling cascades. Recently, it hasbeen shown that mechanistic target of rapamycin (mTOR) signaling, comprised mainly of mTORC1 signaling, plays a critical role in IL-17 expression. Here, we review the current knowledge regarding mechanisms by which mTORC1 regulates IL-17 expression. mTORC1 posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 102 publications
2
93
0
Order By: Relevance
“…Supporting these findings, GNC2-deficient mice develop a form of EAE characterized by absence of remission (52). In contrast, the mTORC1 pathway regulates metabolic programs to facilitate the switch from quiescent to activated T cell and plays a critical role in Th17 cell differentiation (53,54). Meanwhile, mTORC2 through its substrate SGK1 regulates the ability of Th cells to differentiate into Th2 cells (55,56).…”
Section: Discussionmentioning
confidence: 91%
“…Supporting these findings, GNC2-deficient mice develop a form of EAE characterized by absence of remission (52). In contrast, the mTORC1 pathway regulates metabolic programs to facilitate the switch from quiescent to activated T cell and plays a critical role in Th17 cell differentiation (53,54). Meanwhile, mTORC2 through its substrate SGK1 regulates the ability of Th cells to differentiate into Th2 cells (55,56).…”
Section: Discussionmentioning
confidence: 91%
“…IL-17 can activate nuclear factor κ B (NF- κ B) transcription factors, extracellular signal-regulated protein kinase (ERK1 and ERK2), c-Jun N-terminal kinases (JNK-1 and JNK-2), and mitogen-activated protein kinases (p38 MAPKs) pathways, leading to upregulation of expression of inflammatory cytokines, such as IL-6 and IL-1 [32]. Recent investigations have revealed that mammalian target of rapamycin (mTOR) is a critical signaling pathway for Th17 responses and IL-17 expression [3337]. The mTOR signaling regulates IL-17 expression through hypoxia-inducible factor 1 α (HIF-1 α ) and ribosomal protein S6 kinase (S6K: S6K1 and S6K2) [3740].…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have revealed that mammalian target of rapamycin (mTOR) is a critical signaling pathway for Th17 responses and IL-17 expression [3337]. The mTOR signaling regulates IL-17 expression through hypoxia-inducible factor 1 α (HIF-1 α ) and ribosomal protein S6 kinase (S6K: S6K1 and S6K2) [3740]. mTOR signaling activates HIF-1 α , which promotes IL-17 expression by activating ROR γ t (a key transcriptional regulator of Th17 cells) and mediating degradation of Foxp3 (a key transcriptional regulator of Treg cells) [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mTORC1 pathway is of pivotal importance for metabolic regulation and functioning of innate and adaptive immune cells, as clearly verified by the immunesuppressive function of mTORC1 inhibitors such as rapamycin [7]. Notably, the differentiation of Th17 cells is controlled by mTORC1, which promotes Th17 differentiation [8,9]. Moran et al [10] recently confirmed substantial infiltration of inflammatory Th17 cells with a striking Th17-skewed cytokine profile in HS skin.…”
Section: Hidradenitis Suppurativa · Isotretinoin · Mtor Signalling · mentioning
confidence: 65%